Stochastic optimization model to simulate football games as logistics networks - Menguc, Kenan; Aydin, Nezir (TARU PUBLICATIONS, 2024)
Football industry grows and improves day by day. All successes in universal tournaments results in huge revenue. Since the individual performances of the players determine the performance of the team, players` performances are measured by commercial companies with a higher reliability. Significant football models have been produced from several produced data. The proposed model, in this study, develops an attack routing model based on deviations in players` performances because the performances of players fluctuate from game to game. These fluctuations are handled by incorporating stochasticity. Thus, the developed mathematical model is stochastic and compares attack routes according to variations in performances of players. As a case study, one of the best team, which ranked in top three in its league for last two years, is analyzed and results show the adequacy of the model very clearly.
Keywords: Transshipment problem; Optimization; Spatio-temporal data; Football; Soccer; Stochastic modelling; Chance constraint; PERFORMANCE; LEAGUE; Information Science & Library Science